2018
DOI: 10.12998/wjcc.v6.i15.931
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde intrarenal surgery vs miniaturized percutaneous nephrolithotomy to treat lower pole renal stones 1.5-2.5 cm in diameter

Abstract: AIMTo compare the outcomes of retrograde intrarenal surgery (RIRS) and miniaturized percutaneous nephrolithotomy (mini-PCNL) in treating lower pole (LP) renal stones with a diameter of 1.5-2.5 cm.METHODSA total of 216 patients who underwent mini-PCNL (n = 103) or RIRS n = 113) for LP stones with a diameter of 1.5-2.5 cm were enrolled between December 2015 and April 2017 at the Urology Department of Ningbo Urology and Nephrology Hospital.RESULTSSignificant differences were found in the hospital stay (9.39 ± 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
(20 reference statements)
3
8
0
4
Order By: Relevance
“…Our results con rmed that PCNL offered a higher SFR than RIRS as well, which was consistent with most published studies [8,20,2]. Zewu et al supposed that the potential reasons for RIRS with a relatively lower SFR may be due to residual fragments that are more likely to represent a cluster of clinically insigni cant fragments and small working channel according literatures [25], as well as a call for the vacuum aspiration stone system for RIRS.…”
Section: Correlation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Our results con rmed that PCNL offered a higher SFR than RIRS as well, which was consistent with most published studies [8,20,2]. Zewu et al supposed that the potential reasons for RIRS with a relatively lower SFR may be due to residual fragments that are more likely to represent a cluster of clinically insigni cant fragments and small working channel according literatures [25], as well as a call for the vacuum aspiration stone system for RIRS.…”
Section: Correlation Analysissupporting
confidence: 91%
“…A 4.8F Double-J stent was routinely placed at the end of the operation because of possible edema and other problems that might be caused by the access sheath. For the patients who could not place the access sheaths rightly due to the small diameter of their ureters, and a D-J stent was placed for 2-4 weeks and then perform the surgery [7,8].…”
Section: Rirsmentioning
confidence: 99%
“…Zeng et al found that super-miniPCNL (SMP) had better SFR and lesser auxiliary procedure rate when compared to RIRS for 1-2 cm lower calyceal stones [14]. Several miniature percutaneous techniques (tract size < 22 Fr) have been introduced to provide a less invasive alternative to conventional PCNL (tract size 24-34 Fr) [15] and provide more efficient stone fragmentation and retrieval compared to RIRS [16][17][18][19][20]. Most miniPCNL techniques achieve stone fragmentation using laser or pneumatic lithotripsy and rely on passive irrigation-based siphoning of small stone fragments.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the accumulation of ureteroscopic surgery experience and the rapid improvement of ureteroscope apparatus, the clinical application of RIRS is more extensive. It has been reported that the SFR can reach 73.6% when RIRS is used to treat the 2.0-3.5 cm kidney stones and 90.2% when used to treat LPSs with a diameter of 1.5-2.5 cm [3,8].…”
Section: Introductionmentioning
confidence: 99%